UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN MENYIMAK BAHASA INDONESIA DI SEKOLAH - BARUS SANGGUP (BAHAS, 2013)
This scientific writing is aimed to know the efforts in enhancing the quality of listening instructional in Indonesian language at school. The points to discuss are related to listening instructional, causes of less effective in listening instructional at school, and some efforts to enhance the quality of listening instructional at school. The results of discussion showed that there are some efforts in enhancing the quality of listening instructional at school such as using various and relevant techniques, using relevant listening materials, using various learning medias, managing conducive classroom, implementing good and well evaluation, having correct assumption and giving the training of planning in producing listening instructional materials. Key words : listening instructional, efforts in enhancing the quality